Γ-Pyrone compounds: flavonoids and maltol glucoside derivatives from Herniaria glabra L. collected in the Ternopil region of the Ukraine. (August 2018) - Kozachok, Solomiia; Pecio, Łukasz; Kolodziejczyk-Czepas, Joanna; Marchyshyn, Svitlana; Nowak, Pawel; Mołdoch, Jarosław; Oleszek, Wiesław
Abstract: The phytochemical investigation of the whole plant extracts of Herniaria glabra L. (Caryophyllaceae) led to the identification and isolation of four known flavonoids, one known and three undescribed maltol derivatives, and benzyl β-gentiobioside. The structures were established by extensive 1D and 2D NMR spectroscopic analyses, as well as HRESIMS data. For the first time in Herniaria genus, as well as in Caryophylaceae family the presence of apiorutin quercetin 3- O -[(D-apio-β-d -furanosyl-(1 → 2)- O -[-α-l -rhamnopyranosyl-(1 → 6)]-β-d -glucopyranoside] and licoagroside B maltol 3- O -[6- O -(3-hydroxy-3-methylglutaroyl)]-β-d -glucopyranoside were revealed. Additionally, antioxidant actions of apiorutin, rutin, narcissin (isorhamentin 3- O -β-d -rutinoside) and licoagroside B were assessed in human blood plasma, exposed to the peroxynitrite-induced oxidative stress in vitro . The isolates partly reduced oxidative (oxidation of thiol groups) and nitrative (tyrosine nitration) damage to blood plasma proteins, decreased plasma lipid peroxidation as well as enhanced the non-enzymatic antioxidant capacity of blood plasma. No cytotoxicity of the examined substances towards peripheral blood mononuclear cells was found. Graphical abstract: Image 1 Highlights: Three undescribed maltol glucoside derivatives were isolated from Herniaria glabra. Benzyl gentiobioside, licoagroside B and four known flavonoids were also isolated. Antioxidant actions of apiorutin, rutin, narcissin, licoagroside B were determined. No cytotoxicity of the examined isolates towards PBMCs was observed.